Brexit and the Everyday Politics of Emotion: Methodological Lessons from History. (November 2020) - Moss, Jonathan; Robinson, Emily; Watts, Jake
The 2016 European Union referendum campaign has been depicted as a battle between 'heads' and 'hearts', reason and emotion. Voters' propensity to trust their feelings over expert knowledge has sparked debate about the future of democratic politics in what is increasingly believed to be an 'age of emotion'. In this article, we argue that we can learn from the ways that historians have approached the study of emotions and everyday politics to help us make sense of this present moment. Drawing on William Reddy's concept of 'emotional regimes', we analyse the position of emotion in qualitative, 'everyday narratives' about the 2016 European Union referendum. Using new evidence from the Mass Observation Archive, we argue that while reason and emotion are inextricable facets of political decision-making, citizens themselves understand the two processes as distinct and competing.